The SPI-1-like Type III secretion system: more roles than you think. - Egan, Frank; Barret, Matthieu; O'Gara, Fergal (Frontiers in Plant Science, 2014)
The type III secretion system (T3SS) is a protein delivery system which is involved in a wide spectrum of interactions, from mutualism to pathogenesis, between Gram negative bacteria and various eukaryotes, including plants, fungi, protozoa and mammals. Various phylogenetic families of the T3SS have been described, including the Salmonella Pathogenecity Island 1 family (SPI-1). The SPI-1 T3SS was initially associated with the virulence of enteric pathogens, but is actually found in a diverse array of bacterial species, where it can play roles in processes as different as symbiotic interactions with insects and colonisation of plants. We review the multiple roles of the SPI-1 T3SS and discuss both how these discoveries are changing our perception of the SPI-1 family and what impacts this has on our understanding of the specialisation of the T3SS in general.